HIV-Associated Dementia: Pathogenesis, Risk Factors, Diagnosis, and Management – A Literature Review - Baiq Tasyfa Hasya Auliya Tsaniya; Fidelya Fitria Hakim; I Wayan Putra Kesumantara; Sheilla Ninditya Putri; Herpan S. Harahap (Jurnal Biologi Tropis, 2026)
HIV-associated dementia (HAD) is the most severe form of HIV-associated neurocognitive disorders (HAND), characterized by significant cognitive impairment and decline in daily functioning. Despite the widespread use of antiretroviral therapy (ART), neurocognitive impairment remains an important clinical challenge among people living with HIV. This review aimed to summarize current evidence regarding the pathogenesis, diagnosis, risk factors, and management of HIV-associated dementia. The study was conducted using a literature review method by examining relevant scientific articles and publications discussing HIV-associated dementia and HIV-associated neurocognitive disorders. The findings indicate that HIV enters the central nervous system through the Trojan horse mechanism, infects microglia and macrophages, and induces chronic neuroinflammation, leading to neuronal damage and cognitive decline. Major risk factors include severe immunosuppression, advanced age, comorbidities, and social determinants. Diagnosis is established based on the Frascati criteria and supported by cognitive screening instruments. Antiretroviral therapy remains the cornerstone of treatment and may be complemented by cognitive rehabilitation and psychosocial support. In conclusion, HAD is a complex neurocognitive complication of HIV infection that continues to affect patients despite advances in ART. Early detection and multidisciplinary management are essential to preserve cognitive function and improve quality of life. Further studies are recommended to improve early screening strategies and develop more effective interventions for HIV-associated cognitive impairment.